PPP-RTK platform performance based on single-frequency GPS data - Odijk, Dennis; Teunissen, Peter; Zhang, Baocheng (2011)
As an improvement over 'conventional' PPP, Real-Time Kinematic Precise Point Positioning (PPP-RTK) is a promising technique for high-precision (cm-level) carrier-phase based remote sensing platform positioning. The key to obtain these very precise positions is that the user should be able to resolve the ambiguities in the phase data to their integer values, as then his phase data starts to act as if they were very precise code data. In order to do so, the user needs to apply corrections to his GPS data. In addition to corrections for the satellite clocks and ionospheric delays, as with 'conventional' PPP, crucial to restore the integerness of the ambiguities is that the PPP-RTK user needs appropriate corrections for the satellite phase hardware biases. In our approach these corrections are determined by a regional network of CORS stations. To provide the most precise corrections to the PPP-RTK user, the corrections should be based on a solution in which the network ambiguities are resolved to their integer values. Furthermore, in our approach the ambiguity-fixed network ionospheric delays are interpolated to the approximate user location. So far very fast -even instantaneous- PPP-RTK integer ambiguity resolution performance has been reported based on dual-frequency GPS data. However, the technique becomes more attractive when it can be applied to users that operate with low-cost mass-market single-frequency receivers as well. In this contribution we demonstrate that our PPP-RTK approach can be applied to these users without any modification. Results are presented of the performance of single-frequency PPP-RTK for both a high-grade and a low-grade GPS receiver.The conclusion reads that single-frequency PPP-RTK integer ambiguity resolution is feasible, even using a low-cost receiver: following an initialization time of less than 5 minutes the correct integers can be resolved in real-time, thus providing cm-level positioning.